Structural ownership and ESG disclosure: Unveiling their impact on corporate financial performance - Wardani, Isma Aprilylyani; Juanda, Ahmad; Wicaksono, Agung Prasetyo Nugroho (Journal of Accounting and Investment, 2025)
Research aims: This study aims to provide empirical evidence on the crucial role of ownership structure in encouraging or hindering the transparency of environmental, social, and governance (ESG) information in Indonesian companies and the effect of ESG on corporate financial performance.Design/Methodology/Approach: This study’s sample consists of 64 non-financial companies listed on the Indonesia Stock Exchange in 2023. The data were collected from financial reports and corporate sustainability reports, the Indonesia Stock Exchange database, Bloomberg, and Google search results. In addition, multiple linear regression tests were used to test the hypothesis parameters.Research findings: The results showed a positive and significant relationship between management, foreign, institutional, public, and state ownership with ESG disclosure. On the other hand, family ownership with ESG disclosure. In addition, the study noted that ESG disclosure is positively correlated with ROE and ROIC but negatively correlated with ROA, indicating that companies that focus on ESG may face a decrease in short-term profitability but tend to be more sustainable in the long term.Theoretical contribution/ Originality: This study is one of the few that examines the influence of ownership structures such as managerial, foreign, institutional, public, state, and family ownership on ESG disclosure in Indonesia non-financial companies. This study uses ROIC as an underutilized financial performance indicator. It offers relevant empirical insight in the Indonesian context, which has not been explored in global studies on ESG and ownership structure. Practitioner/Policy implication: Diverse ownership structures affect ESG disclosures and financial performance, urging management to prioritize transparency and policymakers to incentivize robust ESG practices, especially in family ownership firms.Research limitation/Implication: The study is limited by its focus on Indonesia, and future research can expand by conducting cross-country analyses of ownership structures on ESG disclosure and corporate financial performance.